1985
DOI: 10.1136/pgmj.61.722.1043
|View full text |Cite
|
Sign up to set email alerts
|

Plasma arginine vasopressin in hyponatraemic patients receiving diuretics

Abstract: Summary:Random estimations of plasma arginine vasopressin concentration were undertaken in 6 non-oedematous patients receiving diuretic therapy for hypertension, who were admitted to hospital with severe hyponatraemia. Hyponatraemia resolved within 2 weeks of discontinuing the diuretic. Measurable amounts of plasma arginine vasopressin were detected in all 6 patients.Sequential biochemical measurements in one patient, performed when plasma sodium concentration and osmolality were returning to the normal range,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 9 publications
(13 reference statements)
0
13
0
Order By: Relevance
“…First, they inhibit electrolyte transport at the cortical diluting sites, thereby raising the minimum urinary osmolality [7,9,10]; but while this effect reduces electrolyte free water clearance [5], it does not reduce urine flow and therefore does not directly predispose to an expansion of total body water. Second, thiazides stimulate antidiuretic hormone (ADH) release [11][12][13]. Third, they decrease the glomerular filtration rate acutely [9,10,14,15] and increase fractional proximal water reabsorption [15], thereby reducing delivery to diluting sites.…”
Section: Mechanismsmentioning
confidence: 99%
See 3 more Smart Citations
“…First, they inhibit electrolyte transport at the cortical diluting sites, thereby raising the minimum urinary osmolality [7,9,10]; but while this effect reduces electrolyte free water clearance [5], it does not reduce urine flow and therefore does not directly predispose to an expansion of total body water. Second, thiazides stimulate antidiuretic hormone (ADH) release [11][12][13]. Third, they decrease the glomerular filtration rate acutely [9,10,14,15] and increase fractional proximal water reabsorption [15], thereby reducing delivery to diluting sites.…”
Section: Mechanismsmentioning
confidence: 99%
“…Similarly, Abramow and Cogan [4] found that in some of their patients the fractional urea excretion was high during hyponatremia and fell with correction of the serum sodium. Furthermore, many patients with thiazide-induced hyponatremia appear euvolemic [4,12,[23][24][25][26]. Finally, in some of them water balance was positive during the development of hyponatremia and negative during its correction [4,17,24,25,27].…”
Section: Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…Vasopressin receptor antagonists block arginine vasopressin from binding to V2 receptors in the distal nephron and promote the excretion of electrolyte-free water. 16 In recent randomized trials, tolvaptan, an orally active V2 receptor antagonist, has been effective in raising serum sodium in patients with hyponatremia.…”
Section: Discussionmentioning
confidence: 99%